2D TO 3D RESISTIVITY IMAGING ON DETERMINIG THE VOLUME OF SINKHOLE : STUDY CASE IN KAMPAR - Binti Osman Ash’ari, Nadia Ashikin (Universiti Teknologi PETRONAS, 2016)
A geophysical study was conducted at area Mukim Kampar using 2D Electrical Resistivity Technique (ERT) to study subsurface analysis. The study area is in the Kinta Limestone Formation. The study area lies within the Kinta limestone formation which is characterized by weak soils overlying limestone bedrock with karstic features such as pinnacles, solution channels, cavities, cliffs, overhangs and steep depression amidst rock plateau. The objective of this subsurface analysis is to study the subsurface of limestone features using Electricity Resistivity Imaging, to produce resistivity map (isoelectric) at the study area and to generate 3D model at the subsurface limestone features.